Medical cannabis utilization in children – a study based on a nationwide cohort - Treves, Nir; Yakirevich-Amir, Noa; Allegaert, Karel; van den Anker, John N.; Kohn, Elkana; Berlin, Maya; Hazan, Ariela; Davidson, Elyad; Berkovitch, Matitiahu; Bonne, Omer; Stolar, Orit E.; Matok, Ilan (Frontiers in Pharmacology, 2025)
IntroductionThis study aimed to evaluate the utilization of medical cannabis in a pediatric population and compare short-term persistence rates with those in adolescents and young adults.MethodsIn this retrospective, nationwide cohort study supplemented by data from an open-label study of children with ASD, patient cases under 12 years of age who received medical cannabis treatment between 2018 and 2022 were analyzed. The primary outcome assessed was treatment persistence within the first 3 months. Secondary outcomes included changes in THC ratios, amounts dispensed, and reasons for treatment discontinuation.ResultsThe patient population consisted of 1,341 children using medical cannabis for ASD (751), epilepsy (330), Tourette syndrome (165), and pediatric cancer (95). Out of 3,007 consecutive medical cannabis sessions, the adjusted hazard ratio for discontinuation in the first 3 months was 0.83 (95% CI [0.71–0.96], p = 0.01) for young adults compared to children. Approximately 60%–70% of children discontinued therapy within the first 6 months. Significant alterations in THC ratios or dispensed amounts were observed in most sessions within the initial 6 months. In the open-label study dataset, most treatment discontinuations were primarily attributed to adverse effects and a perceived lack of therapeutic efficacy.ConclusionOur findings suggest that short-term persistence of medical cannabis therapy is lower in children compared to adolescents and young adults. Moreover, many pediatric patients required adjustments to their THC ratios and showed a high frequency of treatment discontinuation. These observations underscore the importance of targeted strategies to improve medical cannabis treatment effectiveness and adherence in the pediatric population. Although MC may offer therapeutic benefits for pediatric patients, our findings emphasize the importance of careful patient selection and close medical follow-up to optimize clinical outcomes.